Stem Cells: Controlled Exposure of Bioactive Growth Factor in 3D Amyloid Hydrogel for Stem Cells Differentiation (Adv. Healthcare Mater. 18/2017). Issue 18 (20th September 2017) - Das, Subhadeep; Kumar, Rakesh; Jha, Narendra Nath; Maji, Samir K.
Abstract : Samir K. Maji and co‐workers present an amyloid hydrogel for sustained growth factors delivery in tissue engineering applications in article number 1700368 . The image represents stem cells (blue spheres) embedded within the amyloid hydrogel matrix (grey network) encapsulating growth factors (green dots). Within 3D culture, stem cells self‐organizes into spheroids (red sphere) with up‐regulated neural genes. In three‐dimensional cell culture, the entrapped growth factors within hydrogel and the surface property of amyloids promoted stem cells into neuro‐sphere formation and higher neuronal gene expression.